CHANNELS, WATER SUPPLY AND IRRIGATION SYSTEMS IN LIMA: THE CASE OF HUATICA CHANNE - Pérez Chávez, Paul (2010)
The aim of this article is to explain how water supply and the irrigations on the left bank of the Rímac River produced in the new society who settled after the Conquest. Besides, we will develop some water supply features, used in Colonial Times and finally we will talk about an important irrigation canal called Huatica. This canal, built in Pre-hispanic times, will give us a clear idea of the development regarding water use for irrigation, the economic exploitation to which it was subjected and its use for the cleanliness and hygiene of the city and its importance as an element of the original draining system in Lima.